ANALYSIS OF CURRENT ACCOUNTING PRACTICES AND CHALLENGES IN AGRICULTURAL ENTERPRISES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Agricultural enterprises play a critical role in the economic development of Uzbekistan, contributing to food security, employment, and GDP growth. However, their financial reporting practices remain outdated, relying heavily on local standards that fail to meet international requirements. This study analyzes the current accounting practices in Uzbekistan’s agricultural sector, identifies key challenges in transitioning to International Financial Reporting Standards (IFRS), and highlights the barriers to implementing IAS 41 ("Agriculture"). The findings reveal gaps in market data availability, regulatory misalignment, and skill deficiencies among accounting professionals. Recommendations for overcoming these challenges include capacity-building initiatives, regulatory reforms, and the adoption of digital technologies to facilitate accurate and transparent financial reporting.